Development of a Commercial Manufacturing Process of 9-[(R)-2- (phosphonomethoxy)propyl] adenine (PMPA): A Key Intermediate for the Production of Tenofovir-based HIV Medicines - Mbutho, Banele (University of the Witwatersrand, Johannesburg, 2023)
South Africa runs the largest antiretroviral (ARV) program in the world and yet 99% of the active pharmaceutical ingredients (APIs) used to make ARVs are imported from China. Dependence on imported APIs has major cost implications and influences the medication’s security of supply. This project was concerned with making it possible to produce the APIs tenofovir, a precursor for tenofovir disoproxil fumarate and tenofovir alafenamide locally and at a lower cost. A new synthetic route recently introduced by Medicines 4 All (M4ALL) was studied and used in this dissertation. The four-step process that produces an adenine derivative was optimized and scaled into a commercial industrial process producing tenofovir intermediates in repeatable yield and purity. This route was determined to be the most cost-effective since it utilized low cost and commercially available diaminomaleonitrile and triethyl orthoformate as starting materials—contrary to the synthetic routes currently used by the 17 largest tenofovir manufacturers. Key process improvements included a decrease in the number of solvents used and the minimization of by-product formation. Results showed that high yields of tenofovir intermediates were successfully synthesized using this new route. As such, the chemical company we conducted this research in, Chemical Process Technology Pharma will be able to employ this synthetic methodology to affordably produce the APIs used in the manufacturing of ARVs locally improving access to affordable medication.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Pharmaceutical; Intermediate; Tenofovir; Process; Commercial; UCTD; SDG-3: Good health and well-being